A Unique Drachm Coin of Shapur I - Yücel, M. (Routledge, 2017)
The Sasanian king Shapur I held a ten year series of campaigns against the Roman Empire. Returning to Iran after these campaigns, in order to immortalize his victories he built a series of reliefs and gave broad information in his famous work, Ka’be-ye Zardosht. However, the term he used to define himself in these articles, “King of Kings of Iranians and non-Iranians,” was not used on coins, which has become a subject of discussion. This work aims to clarify such arguments based on a unique drachm belonging to Shapur I which is present in the Elazig Museum of Archaeology and Ethnography. © 2017 Association For Iranian Studies, Inc.